A rare case of dorsolumbar intradural cavernous hemangioma - Binoy Damodar Thavara; Rajeev Mandaka Parambil; Byjo Valiyaveetil Jose; Geethu G. Nair; Prem kumar Sasi; Gorijavolu Saisree Krishna (Egyptian Journal of Neurosurgery)
Abstract Background Intradural extramedullary (ID-EM) cavernous hemangioma (CH) is rare and only 71 cases are reported in the literature. Authors present a very rare case of dorsolumbar intradural CH adhering to both nerve root and dura mater. Case presentation Authors report a rare case of intradural CH at D12-L1 level presenting with low back ache and left lower limb radiating pain for the past 7 years. Magnetic resonance imaging (MRI) scan showed changing intensity of the lesion compared to the old MRI scan taken 7 years back. Lesion showed heterogenous contrast enhancement with irregular surface. At surgery, dura was opened and a reddish grey, thin walled, mulberry-like lesion with multiple small lobulations on the surface was seen. It was arising from a root and also adhering to the anterior dura mater. The lesion was seen below the level of conus and surrounded by roots. En-bloc excision was done and diagnosis was confirmed by histological examination. Patient improved in postoperative period. Conclusions Spinal intradural CH adhering to both nerve root and dura mater is very rare. They can show a benign course for long duration of time with changing MRI characteristics. It can show heterogenous contrast enhancement with irregular surface. They appear as mulberry-like lesion and en-bloc excision is the treatment of choice.